Slough House : Real Tigers - Book 3 - Herron, Mick (New York, NY : Soho Crime, 2016)
"Slough House is the MI5 branch where disgraced operatives are reassigned after theyve messed up too badly to be trusted with real intelligence work. The Slow Horses, as the failed spies of Slough House are called, are doomed to spend the rest of their careers pushing paper, but they all want back in on the action. When one of their own is kidnapped and held for ransom, the agents of Slough House must defeat the odds, overturning all expectations of their competence, to breach the top-notch security of MI5s intelligence headquarters, Regents Park, and steal valuable intel in exchange for their comrades safety"-- Dust jacket flap.
"A novel"--Jacket.
Keywords: Great Britain. -- MI5 -- Officials and employees; Fiction; Kidnapping -- Fiction; Conspiracies -- Fiction; London (England) -- Fiction; Spy fiction; Detective and mystery fiction; Thrillers (Fiction)